Studi Kritis Bahan Ajar PABP Materi Gibah dan Tabayun di Kelas 7 SMPIT Takhassus Al-Qur’an Ashabiq Sukabumi - Ressy Resviati Putri; Siti Qomariyah; Ai Siti Rahmawati; Lia Aliyah; Leni Sumarni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to conduct a critical study of the teaching materials for Islamic Religious Education and Character Building (PABP), specifically on the material